Improving the Organizational and Economic Mechanism of Service Industry Development (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article explores organizational-economic forms and tools of improving the quality and efficiency of labor in the service sector. And also the methods of dialectical and systematic approach, integrated assessment, comparative and comparative analysis of statistical and dynamical approach and methods of the group, and presented various insights on improvement of mechanisms of development of sphere of services